Sarjana (Sarana Belajar Anak Jalanan): Pemberdayaan Anak Jalanan Mandiri, Kreatif Dan Inovatif Melalui Pendidikan Kewirausahaan - Basam, Fajri; Amal, Amri (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Makassar city is one of the cities in Indonesia that can not be separated from the problem of street children. Street children are a very vulnerable social group from various acts of violence, whether physical, emotional, sexual or social violence. Therefore, through the program of dedication to the community intend to participate actively in solving the problems of street children through the program